2007
DOI: 10.1002/mrm.21342
|View full text |Cite
|
Sign up to set email alerts
|

Oxygenation and hematocrit dependence of transverse relaxation rates of blood at 3T

Abstract: Knowledge of the transverse relaxation rates R 2 and R* 2 of blood is relevant for quantitative assessment of functional MRI (fMRI) results, including calibration of blood oxygenation and measurement of tissue oxygen extraction fractions (OEFs). In a temperature controlled circulation system, these rates were measured for blood in vitro at 3T under conditions akin to the physiological state. Single spin echo (SE) and gradient echo (GRE) sequences were used to determine R 2 and R 2 * , respectively. Both rates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
280
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(296 citation statements)
references
References 32 publications
(72 reference statements)
13
280
3
Order By: Relevance
“…A quadratic model was used to describe the blood transverse relaxation rate R2* as a function of fractional blood oxygenation (Y)8, 9: normalR2*=normalA*+normalB*(1Y)+normalC*(1Y)2where A*, B*, and C* are empirically derived coefficients dependent on B 0 and Hct.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A quadratic model was used to describe the blood transverse relaxation rate R2* as a function of fractional blood oxygenation (Y)8, 9: normalR2*=normalA*+normalB*(1Y)+normalC*(1Y)2where A*, B*, and C* are empirically derived coefficients dependent on B 0 and Hct.…”
Section: Methodsmentioning
confidence: 99%
“…Coefficients A*, B*, C* previously measured empirically for Hct in the range 0.21–0.57 at 3T9 were used to obtain R2*(Hct,Y) values in the full range of blood oxygenation fractions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current studies, perfusion was increased during sustained hypoxia, 12 and the arterial and venous compartments contain increased deoxyhemoglobin, so blood oxygenation level-dependent changes will add to the observed reduction in T 2,index . From Zhao et al, 13 for a hematocrit of 0.44 the transverse relaxation rate, R 2 , can be approximated in terms of oxygen saturation, Y, as:…”
Section: Diffusion-weighted Mri Changes In Acute Mountain Sickness Jsmentioning
confidence: 99%
“…[36][37][38][39][40][41][42][43][44] Additionally, concentration of other molecules relevant to lymphatic function will influence the water T 2 . It has been shown that in agarose phantoms water T 2 increases with increasing levels of NaCl.…”
Section: Physiology Of Deep and Superficial T 2 Changesmentioning
confidence: 99%